Down with Consumption! Chronicle of a popular riot in Toledo - Velasco García, Daniel (Hispania Nova, 2026)
The serious economic and social situation in which the Spanish peasantry found itself during the last moments of the 19th century and the first years of the 20th produced different riots and tumults in ci-ties throughout the country. One of them was the one found on March 15th 1913 in Toledo after the murder of the young Antonio Campuzano. After this, a crowd burned the booths where taxes were collected and demanded that the authorities put an end to the abuses. This paper tries to analyze this fact the social exaltation of the days after the mur-der through the chronicles collected in local, regio-nal and provincial newspapers.